The Stock Clearing Corporation - Richter, Frederic Ernest (Quarterly Journal of Economics, 1920)
Journal Article The Stock Clearing Corporation Get access Frederic Ernest Richter Frederic Ernest Richter New York City Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 34, Issue 3, May 1920, Pages 538–544, https://doi.org/10.2307/1883366 Published: 01 May 1920